An empirical typology of travel-to-work areas in Argentina based on sectoral profiles of territorial coagglomeration - Calá, Carla Daniela (2019)
Spatial location of economic activities is a central aspect for the analysis of a country's productive structure and the design of productive development policies. In developed countries there is a large number of investigations that describe regional specialization profiles within a single country and explain the observed patterns based on different factors, such as the existence of economies of scale, the endowment of natural resources or fiscal incentives. The specialization profile is also typically used as an input to explain the economic performance of the regions in terms of employment growth, productivity or value added (Frenken et al., 2007; Bishop and Gripaios, 2010; van Oort et al., 2015; Cortinovis and van Oort, 2015). Besides, the evolution of regional specialization profiles can be used to illustrate or describe processes of structural change.